2017
DOI: 10.25127/aps.20171.356
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación del contenido de metales pesados (Cd y Pb) en diferentes edades y etapas fenológicas del cultivo de cacao en dos zonas del Alto Huallaga, Huánuco (Perú)

Abstract: <p>La presencia de metales pesados en los productos agrícolas por encima de los límites máximos permisibles está generando una gran preocupación para los agricultores. En base a esto, el presente estudio se desarrolló con el objetivo de determinar el contenido de estos metales pesados en el cultivo de cacao. Para ello, se realizó la evaluación de parámetros del suelo, de hojas y de la almendra del cacao en cuatro parcelas de agricultores de cacao orgánico pertenecientes a la Cooperativa Agraria Industria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In the specific case of cocoa, this peruvian agro-export product has high consumption worldwide in all social strata. On the other hand, various studies [15,18,[26][27][28] have confirmed the presence of traces of Cd, potentially toxic, which has forced the Peruvian State to enacted Ministerial Resolution, No. 0449-2018-MINAGRI [29]: Rapid impact agenda linked to maximum levels of cadmium in specific products such as cocoa and chocolate.…”
Section: Introductionmentioning
confidence: 99%
“…In the specific case of cocoa, this peruvian agro-export product has high consumption worldwide in all social strata. On the other hand, various studies [15,18,[26][27][28] have confirmed the presence of traces of Cd, potentially toxic, which has forced the Peruvian State to enacted Ministerial Resolution, No. 0449-2018-MINAGRI [29]: Rapid impact agenda linked to maximum levels of cadmium in specific products such as cocoa and chocolate.…”
Section: Introductionmentioning
confidence: 99%